Method for improving performance of high-strength and high-conductivity copper-silver alloy and copper-silver alloy

Through vacuum induction smelting, forging, heat treatment, cold rolling and other processes, high-strength, high-conductive copper-silver alloys were prepared, solving the problem of difficult balance between strength and conductivity in the existing technology, and achieving a coordinated improvement of high strength and excellent conductivity.

CN119876804AActive Publication Date: 2025-04-25HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510147717.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-25
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

While the existing copper-silver alloys are improved, it is difficult to maintain excellent conductivity, which makes it difficult to balance between high strength and high conductivity.

Method used

Through vacuum induction smelting, multiple forging and heat treatment, cold rolling treatment and other processes, copper-silver alloys of high-purity copper and high-purity silver are prepared to achieve grain refinement, precipitation, solid solution, dislocation and fiber reinforcement, and jointly improve conductivity and strength.

Benefits of technology

The produced copper-silver alloy has a tensile strength of more than 1000MPa and a conductivity of more than 70% IACS. It is suitable for new energy vehicle motor rotors, battery management systems, high-speed rail contact lines and large scientific devices with strong magnetic fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876804A_ABST
    Figure CN119876804A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy materials, and particularly relates to a method for improving the performance of a high-strength and high-conductivity copper-silver alloy and the copper-silver alloy. The method for improving the performance of the high-strength and high-conductivity copper-silver alloy comprises the following steps that S1, high-purity copper and high-purity silver serve as raw materials, and after vacuum induction melting, casting and solidification are conducted in sequence, a copper-silver alloy cast ingot is obtained; s2, the copper-silver alloy cast ingot obtained in the step S1 is subjected to multiple times of forging and pressing, heat treatment is conducted once after each time of forging and pressing, then natural cooling is conducted to the room temperature, and a homogenized ingot blank is obtained; s3, the homogenized ingot blank obtained in the step S2 is subjected to cold rolling treatment; a copper-silver alloy sample is obtained; and S4, the copper-silver alloy sample obtained in the step S3 is subjected to surface treatment, and the high-strength and high-conductivity copper-silver alloy is obtained. The tensile strength of the high-strength conductive copper-silver alloy prepared through the method can reach 1000 MPa or above, and the conductivity of the high-strength conductive copper-silver alloy can reach 70% IACS or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a method for improving the performance of a high-strength and high-conductivity copper-silver alloy and a copper-silver alloy. Background Art

[0002] High-strength and high-conductivity copper-silver alloys are usually used in large scientific facilities such as strong magnetic fields, new energy vehicles, and other fields. They mainly provide high-strength, high-conductivity, and high-thermal conductivity metal materials for magnets of large scientific facilities with strong magnetic fields, motor rotors of new energy vehicles, high-speed rail contact lines, and other parts. High strength and high conductivity are a pair of contradictory parameters in the research and development and preparation of copper-based conductive materials, that is, the increase in strength is usually accompanied by a decrease in conductivity, which brings many difficulties to the research and development and use of copper-silver alloys.

[0003] In the current copper-silver alloy preparation process, the choice of heat treatment method, time and temperature will have a decisive influence on the alloy crystal structure; therefore, choosing appropriate processing technology and heat treatment method will help to maximize the alloy performance and balance the strength and conductivity of the copper-silver alloy to the greatest extent.

[0004] How to scientifically and rationally design an appropriate preparation technology and method to improve the strength of the copper-silver alloy while ensuring that the copper-silver alloy still has excellent conductivity is one of the key concerns of researchers in this field.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a method for improving the performance of a high-strength and high-conductivity copper-silver alloy and a copper-silver alloy; the tensile strength of the high-strength and high-conductivity copper-silver alloy prepared by the method can reach above 1000 MPa, and the electrical conductivity can reach above 70% IACS.

[0007] In order to overcome the deficiencies of the prior art, the present invention provides the following technical solutions:

[0008] A method for improving the performance of a high-strength and high-conductivity copper-silver alloy comprises the following steps:

[0009] S1. Using high-purity copper and high-purity silver as raw materials, successively subjecting them to vacuum induction melting, casting and solidification to obtain a copper-silver alloy ingot;

[0010] S2, forging the copper-silver alloy ingot obtained in step S1 for multiple times, performing a heat treatment after each forging, and then naturally cooling to room temperature to obtain a homogenized ingot;

[0011] S3, cold rolling the homogenized ingot obtained in step S2 to obtain a copper-silver alloy sample;

[0012] S4. Surface treatment is performed on the copper-silver alloy sample obtained in step S3 to obtain a high-strength and high-conductivity copper-silver alloy.

[0013] Further, in step S1, the high-purity copper is copper particles with a purity of 99.999% and a particle size of φ3×3mm; the high-purity silver is silver particles with a purity of 99.99% and a particle size of φ2×5mm;

[0014] And / or, the usage ratio of high-purity copper to high-purity silver is 76:24.

[0015] Furthermore, in step S1, the vacuum induction melting process specifically includes the following steps:

[0016] (1) The raw materials are placed in a vacuum melting furnace, and the furnace body is pre-evacuated. When the vacuum degree is 1Pa, argon is introduced to make the pressure in the furnace 50kPa, and the addition of argon is stopped; the vacuum is continued to be reduced to 1Pa, and argon is introduced again to make the pressure in the furnace 50kPa; the vacuum is then reduced to 1Pa, and then high vacuum is continued to be drawn to 4.8×10 -3 Pa;

[0017] (2) Argon gas is introduced to 50 kPa, and the furnace heating module is turned on for smelting. The initial heating current is 4.5 A, and then it is increased to 20-22 A at a rate of 1 A per minute. At this time, the temperature inside the furnace is 1000-1100°C. Maintain it for 10-15 minutes to complete the smelting.

[0018] Further, in step S1, a circulating water cooling structure mold is used for casting; the mold temperature is maintained at 22-24°C;

[0019] and / or, the setting time is 2 to 3 hours;

[0020] And / or, after solidification, the ingot is subjected to rough surface processing and then polished with sandpaper to obtain a rectangular ingot with a thickness of 22 to 24 mm and no surface cracks.

[0021] Further, in step S2, the process of multiple forging and heat treatment after forging specifically includes the following steps:

[0022] (1) First round forging and heat treatment: The copper-silver alloy ingot is subjected to a first round forging, which consists of multiple forgings, and the pressing amount of each forging is controlled at 0.4 mm to 0.5 mm. After forging, the thickness of the ingot is 20.5 to 21.0 mm; then the forged ingot is placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, the ingot is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper;

[0023] (2) Second forging and heat treatment: The ingot treated in step (1) is subjected to a second round of forging, which consists of multiple forgings, each with a deformation of 10% to 15%, and the thickness of the ingot after final forging is 15.8 to 16.3 mm; then the forged ingot is placed in a heat treatment furnace for heat treatment, and after the heat treatment is completed, it is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper;

[0024] (3) Third forging and heat treatment: The ingot treated in step (2) is subjected to a third round of forging, which consists of multiple forgings, each with a deformation of 10% to 15%, and the thickness of the ingot after final forging is 9 to 10 mm; the forged ingot is then placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, the ingot is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper.

[0025] Furthermore, the conditions for heat treatment after the first forging are: vacuum degree ≤ 100 Pa, temperature 420-450° C., time 1-1.2 h;

[0026] And / or, the conditions for heat treatment after the second forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., time 1-1.2 h;

[0027] And / or, the conditions for heat treatment after the third forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., and time 1-1.2 h.

[0028] Further, in step S3, the cold rolling process includes rough rolling and finish rolling.

[0029] Further, the rough rolling process specifically includes: rough rolling with a two-roll mill; in each round of rolling, the roller pressure of the rolling mill remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the roller pressure of the rolling mill is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is in the range of 7.0mm to 10.0mm, the roller pressure is 0.5mm each time; when the ingot thickness is 3.0mm to 7.0mm, the roller pressure is 0.2mm each time, and when the ingot thickness is 2.0mm to 3.0mm, the roller pressure is 0.15mm each time; when the ingot thickness is less than 2.0mm, the roller pressure is adjusted to 0.1mm, and after the final rolling, the ingot thickness is 1.8mm to 1.9mm;

[0030] And / or, the finishing rolling process specifically includes: finishing rolling with a four-roll rolling mill; in each round of rolling, the rolling mill's roller pressure remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the rolling mill's roller pressure is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is 1.5mm~1.8mm, the roller pressure is 0.1mm each time, when the ingot thickness is 1.0mm~1.5mm, the roller pressure is 0.08mm each time, when the ingot thickness is 0.8mm~1.0mm, the roller pressure is 0.05mm each time, when the ingot thickness is 0.5mm~0.8mm, the roller pressure is 0.02mm each time, the last round of rolling pressure is 0.016mm, and the ingot thickness finally reaches 0.4mm.

[0031] In addition, the present invention also provides a high-strength and high-conductivity copper-silver alloy, which is prepared by the above-mentioned method for improving the performance of the high-strength and high-conductivity copper-silver alloy.

[0032] Furthermore, the tensile strength of the high-strength conductive copper-silver alloy is above 1000 MPa; and the electrical conductivity is above 70% IACS.

[0033] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:

[0034] The high-strength conductive copper-silver alloy finally obtained by the present invention has a tensile strength of more than 1000 MPa and an electrical conductivity of more than 70% IACS through multiple strengthening effects such as grain refinement, precipitation, solid solution, dislocation, fiber, and the synergistic effect of improving conductivity and repairing damage. The alloy can be effectively applied to key parts such as the motor rotor or battery management system of the ever-expanding new energy vehicle, high-speed rail contact lines, and large scientific equipment with strong magnetic fields, and has a promising market prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:

[0036] Figure 1 This is a transmission electron microscopy (TEM) image of the copper-silver alloy prepared in Example 1;

[0037] Figure 2 This is a transmission electron microscopy (HAADF) image of the copper-silver alloy prepared in Example 1;

[0038] Figure 3 The stress-strain curve of the copper-silver alloy obtained in Example 1 subjected to a tensile test;

[0039] Figure 4This is the conductivity distribution diagram of the copper-silver alloy prepared in Example 1 obtained by measuring points along the rolling direction. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0041] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0042] According to a first aspect of the present invention, there is provided a method for improving the performance of a high-strength and high-conductivity copper-silver alloy, comprising the following steps:

[0043] S1. Using high-purity copper and high-purity silver as raw materials, successively subjecting them to vacuum induction melting, casting and solidification to obtain a copper-silver alloy ingot;

[0044] S2, forging the copper-silver alloy ingot obtained in step S1 for multiple times, performing a heat treatment after each forging, and then naturally cooling to room temperature to obtain a homogenized ingot;

[0045] S3, cold rolling the homogenized ingot obtained in step S2 to obtain a copper-silver alloy sample;

[0046] S4. Surface treatment is performed on the copper-silver alloy sample obtained in step S3 to obtain a high-strength and high-conductivity copper-silver alloy.

[0047] In the preparation steps of the present invention, grain refinement occurs in multiple processes such as solidification, forging, and cold rolling; precipitation strengthening and solid solution strengthening mainly occur during solidification; dislocation strengthening mainly occurs during forging and cold rolling; fiber strengthening mainly occurs during multiple cold rolling processes; and improvement of electrical conductivity and damage repair mainly occur during heat treatment. At the same time, it can be clearly seen at the microscopic level that the strengthening is caused by the synergistic effect of multiple microscopic mechanisms such as grain refinement, fiber strengthening, and dislocation strengthening.

[0048] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred embodiment, in step S1, the high-purity copper is copper particles with a purity of 99.999% and a particle size of φ3×3mm; the high-purity silver is silver particles with a purity of 99.99% and a particle size of φ2×5mm;

[0049] Optionally, the usage ratio of high-purity copper to high-purity silver is 76:24.

[0050] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred embodiment, in step S1, the vacuum induction melting process specifically includes the following steps:

[0051] (1) Place the raw materials in a vacuum melting furnace and pre-evacuate the furnace body. When the vacuum is 1Pa, introduce argon to make the pressure in the furnace 50kPa, then stop adding argon; continue to evacuate to 1Pa, introduce argon again to make the pressure in the furnace 50kPa; then evacuate to 1Pa, and repeat this process to ensure that the residual air in the furnace is as little as possible; then continue to evacuate to a high vacuum of 4.8×10 -3 When the pressure reaches 0.04 Pa, stop pumping; select high-purity dry argon (purity 99.999%);

[0052] (2) After the vacuum degree reaches the requirement, argon gas is introduced to 50kPa, and the furnace heating module is turned on for smelting. The initial heating current is 4.5A, and then it is increased to 20-22A at a rate of 1A per minute. At this time, the high-purity copper and high-purity silver particles are melted and evenly mixed into a uniform red and shiny metal liquid. Under the premise of avoiding the metal solution from being too white and smoking, this state is maintained for 10-15 minutes. At this time, the temperature in the furnace is 1000-1100℃, and the smelting is completed.

[0053] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred implementation scheme, in step S1, a circulating water-cooled structure mold is used for casting, and the mold temperature is maintained at 22-24°C to maintain sufficient supercooling to allow the solidification process to proceed smoothly and to ensure that the grains are sufficiently refined during the solidification and crystallization process.

[0054] Before casting, observe whether the metal solution has bubbles. Otherwise, it is necessary to fine-tune the current to ensure that the metal solution does not have bubbles. At this time, the metal solution has good fluidity and can be cast. When casting, it is better to cast smoothly, allowing the metal solution to flow into the mold continuously and uninterruptedly to cool, and avoid uneven casting that causes excessive fluctuations in the solidification interface in the mold. If there is residual solution that has not been poured out in the crucible, the residual solution often contains more impurities and has poor fluidity. It does not need to be forced into the mold. After casting, let the cooling system of the equipment continue to work for at least 2-3 hours to ensure the completion of the solidification process and to allow the ingot to be protected from oxidation and moisture in 50kPa high-purity dry argon. After cooling for 2-3 hours, the furnace body can be opened to take out the ingot.

[0055] The copper-silver alloy ingot obtained in step S1 is subjected to rough surface processing by using machining equipment such as a milling machine, and all the defects on the surface of the ingot are cut cleanly, and finally polished with sandpaper to obtain a rectangular ingot with no surface defects such as cracks, with a size of about 75 to 77 mm in length, 49 to 51 mm in width, and 22 to 24 mm in thickness. Subsequently, multiple forging heat treatments are performed; it should be noted that when the ingot size is required to be larger, the copper-silver alloy ingot obtained in step S1 needs to be subjected to a homogenization process first, that is, the sample is kept at 700°C to 750°C for 1 to 2 hours, and then subjected to multiple forging heat treatments after surface rough processing.

[0056] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred embodiment, in step S2, the process of multiple forging and heat treatment after forging specifically includes the following steps:

[0057] (1) The first round of forging and heat treatment: A large hydraulic press or friction forging machine is used to perform the first round of forging on the copper-silver alloy ingot. This round of forging consists of multiple forgings, and the pressure of each forging is controlled at 0.4mm~0.5mm. After forging, the thickness of the ingot is 20.5~21.0mm. At this time, the grains inside the ingot material are further refined under the action of forging, and a certain number of dislocations are generated. The movement of dislocations is hindered by the action of grain boundaries, defects, etc., and the material begins to harden and the strength begins to increase. At this time, the sample needs to be heat treated for the first time. The forged ingot is then placed in a heat treatment furnace for heat treatment. Heat treatment can effectively repair the decrease in conductivity caused by forging, and can repair micro-damage inside the material and release stress. The heat treatment is carried out in a heat treatment furnace. The forged sample is placed in a heat treatment furnace with a temperature control accuracy of no more than ±2℃. After the heat treatment is completed, it is naturally cooled to room temperature, taken out, and the sample surface is polished with sandpaper;

[0058] (2) Second round of forging and heat treatment: Use a large hydraulic press or friction forging machine to perform a second round of forging on the ingot treated in step (1). The forging process is repeated multiple times, with each deformation amount being 10% to 15%. The final thickness of the ingot after forging is 15.8 to 16.3 mm. At this time, the grains inside the ingot material are further refined under the action of forging, and dislocations continue to be generated. The further movement of dislocations is hindered by the action of grain boundaries, defects, etc., and the material becomes further hardened, the strength is further increased, and the plasticity begins to deteriorate. At this point, the sample needs to be heat treated a second time. The forged ingot is then placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, it is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper.

[0059] (3) The third round of forging and heat treatment: The ingot treated in step (2) is subjected to the third round of forging using a large hydraulic press or a friction forging press. The forging process is repeated multiple times, with each deformation amount being 10% to 15%. The thickness of the ingot after the final forging is 9 to 10 mm. At this time, the grains inside the ingot material are further refined under the action of forging, and dislocations continue to be generated. The movement of dislocations is hindered by the action of grain boundaries, defects, etc., the material becomes hard, and the strength gradually increases. At this time, the sample needs to be subjected to the final heat treatment. Subsequently, the forged ingot is placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, it is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper.

[0060] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred implementation scheme, the conditions for heat treatment after the first forging are: vacuum ≤ 100Pa, temperature 420-450°C, time 1-1.2h; the recrystallization temperature of copper-silver alloy is about 450°C, and the temperature higher than the recrystallization temperature will cause recrystallization and grain growth inside the material, resulting in a decrease in the mechanical properties of the material, an increase in electrical conductivity, and deterioration of the material strength. If the temperature is too low, although the recrystallization and grain growth processes can be avoided, it will not play a role in releasing the internal stress of the material and repairing microscopic damage, so it is necessary to select a temperature within a certain range for heat treatment.

[0061] Optionally, the conditions for heat treatment after the second forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., time 1-1.2 h;

[0062] Optionally, the conditions for heat treatment after the third forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., and time 1-1.2 h.

[0063] The heat treatment conditions are preferably controlled within the scope of the present invention. If the temperature is too high or the heat treatment time is too long, recrystallization and grain growth will occur, resulting in decreased mechanical properties and a surge in electrical conductivity, which will deteriorate the alloy properties. In addition, after the heat treatment is completed, it is preferred to use natural cooling. If other cooling methods are used, the alloy properties will be affected. For example, water cooling will form a thick oxide layer on the alloy surface, thereby affecting the electrical conductivity of the alloy.

[0064] In the above method for improving the performance of high-strength and high-conductivity copper-silver alloy, as a preferred embodiment, in step S3, cold rolling treatment refers to rolling at room temperature, which includes rough rolling and then finish rolling.

[0065] In particular, the rough rolling process specifically includes: rough rolling with a two-roll mill; in each round of rolling, the roller pressure of the rolling mill remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the roller pressure of the rolling mill is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is in the range of 7.0mm to 10.0mm, the roller pressure is 0.5mm each time; when the ingot thickness is 3.0mm to 7.0mm, the roller pressure is 0.2mm each time, and when the ingot thickness is 2.0mm to 3.0mm, the roller pressure is 0.15mm each time; when the ingot thickness is less than 2.0mm, the roller pressure is adjusted to 0.1mm, and after the final rolling, the ingot thickness is 1.8mm to 1.9mm;

[0066] In particular, the finishing rolling process specifically includes: finishing rolling with a four-roller mill; in each round of rolling, the roller pressure of the rolling mill remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the roller pressure of the rolling mill is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is 1.5mm~1.8mm, the roller pressure is 0.1mm each time, when the ingot thickness is 1.0mm~1.5mm, the roller pressure is 0.08mm each time, when the ingot thickness is 0.8mm~1.0mm, the roller pressure is 0.05mm each time, when the ingot thickness is 0.5mm~0.8mm, the roller pressure is 0.02mm each time, the last round of rolling pressure is 0.016mm, and the ingot thickness finally reaches 0.4mm.

[0067] The above rolling process is carried out at room temperature without heating. After multiple rolling passes, a large number of dislocations and fibrous structures appear inside the material, the grains are further refined and fiberized, and the strength of the material is significantly improved. This is the result of the synergy of processing strengthening, fiber strengthening, grain refinement and other effects that lead to the improvement of alloy strength.

[0068] Finally, the sample obtained by cold rolling is surface treated by grinding with sandpaper with a mesh size greater than 1000 to obtain a copper-silver alloy with a smooth surface, high strength and high conductivity.

[0069] According to a second aspect of the present invention, a high-strength and high-conductivity copper-silver alloy is provided, which is prepared by the above-mentioned method for improving the performance of the high-strength and high-conductivity copper-silver alloy. The tensile strength of the prepared high-strength and high-conductivity copper-silver alloy is above 1000 MPa; and the electrical conductivity is above 70% IACS.

[0070] The present invention will be described in detail below in conjunction with embodiments of the present invention, and each example is provided by way of explanation of the present invention without limiting the present invention. In fact, it will be clear to those skilled in the art that modifications and variations may be made in the present invention without departing from the scope or spirit of the present invention. For example, a feature shown or described as a part of an embodiment may be used in another embodiment to produce yet another embodiment. Therefore, it is desired that the present invention includes such modifications and variations within the scope of the appended claims and their equivalents.

[0071] In the embodiments of the present invention, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0072] Example 1

[0073] This embodiment provides a method for improving the performance of a high-strength and high-conductivity copper-silver alloy, which specifically includes the following steps:

[0074] ① Raw material preparation: The raw materials are high-purity copper particles with a purity of 99.999% and a size of φ3×3mm, and high-purity silver particles with a purity of 99.99% and a size of φ2×5mm; the crucible is a graphite crucible, the surface of which is cleaned with alcohol and naturally air-dried; the mold is a water-cooled copper mold with a boron nitride release agent sprayed on the surface, and does not need to be preheated when placed in a high vacuum induction melting furnace.

[0075] ② Induction melting: (1) Loading. The equipment used in the laboratory is a 1kg-class high-vacuum melting furnace, which is equipped with a mechanical pump group and a molecular pump group. Taking the melting of 1kg copper-silver alloy ingot as an example, 760g of high-purity copper particles and 240g of high-purity silver particles are placed in a clean graphite crucible. (2) Replace the gas in the furnace and draw a high vacuum. After the raw materials are placed in the high-vacuum melting furnace, the furnace body is closed and pre-vacuumed. When the vacuum is about 1Pa, high-purity dry argon (purity 99.999%) is introduced into it to make the gas pressure in the furnace 50kPa. Stop adding high-purity argon, continue to use the mechanical pump to evacuate to 1Pa, then introduce high-purity argon to a pressure of 50kPa, and then use the pump to evacuate to 1Pa. After repeating this three times, according to the working process of the molecular pump group, turn on the molecular pump group and draw a high vacuum until 4.8×10 -3Pa. (3) Melting. After the vacuum reaches the established requirements, turn off the molecular pump group, introduce high-purity argon gas to 50kPa, turn on the furnace heating module, the initial heating current is 4.5A, and then increase to about 20-22A at a rate of 1A per minute, and maintain this state for 10-15 minutes. At this time, the temperature is about 1000℃~1100℃.

[0076] ③Casting and solidification. Casting is carried out in a high vacuum induction melting furnace. Before casting, observe whether the metal solution has bubbles. Otherwise, it is necessary to fine-tune the current to ensure that the metal solution has no bubbles. At this time, the metal solution has good fluidity and can be cast. The mold is a circulating water-cooled mold, and the temperature is maintained at around 23°C. After casting, let the cooling system of the equipment continue to work for at least 2-3 hours to ensure the completion of the solidification process and to protect the ingot from oxidation and moisture in 50kPa high-purity dry argon. After cooling for 2-3 hours, the furnace body can be opened to take out the ingot.

[0077] ④ Use milling machines and other mechanical processing equipment to perform rough surface processing on the ingot, cut off all defects on the surface of the ingot, and finally polish it with sandpaper to obtain a rectangular ingot with no defects such as cracks on the surface, with a size of approximately 76mm long, 50mm wide and 23mm thick.

[0078] ⑤ The first round of forging and heat treatment. (1) Forging. The above-mentioned ingot is subjected to the first round of forging, which consists of multiple forgings. The pressure of each forging is controlled at 0.4mm~0.5mm. After multiple forgings, the final thickness after forging is about 20.5~21.0mm. (2) Heat treatment. The forged sample is placed in a heat treatment furnace with a temperature control accuracy of no more than ±2℃, and a mechanical pump is used to evacuate the sample. When the vacuum degree drops to no more than 100Pa, heat treatment of the forged sample is started at 450℃ for 1 hour. After keeping warm for 1 hour, cool it naturally to room temperature. Take it out of the furnace and polish the surface of the sample with sandpaper.

[0079] ⑥ Second round of forging and heat treatment. (1) Forging. The above ingot is subjected to a second round of forging. The forging process is repeated several times, and the deformation is ensured to be about 10% to 15% each time. The final thickness after forging is about 15.8 to 16.3 mm. (2) Heat treatment. The forged sample is placed in a heat treatment furnace with a temperature control accuracy of no more than ±2°C, and a mechanical pump is used to evacuate the sample. When the vacuum degree drops to no more than 100 Pa, the forged sample is heat treated at 400°C. After keeping warm for 1 hour, it is cooled naturally to room temperature. Take it out of the furnace and polish the surface of the sample with sandpaper.

[0080] ⑦ The third round of forging and heat treatment. (1) Forging. The above ingot is subjected to the third round of forging. The forging process is repeated many times, and the deformation is ensured to be within the range of about 10% to 15% each time. The final thickness after forging is within the range of 9.0mm to 10.1mm. (2) Heat treatment. The forged sample is placed in a heat treatment furnace with a temperature control accuracy of no more than ±2°C, and a mechanical pump is used to evacuate the sample. When the vacuum degree drops to no more than 100Pa, the forged sample is heat treated at a temperature of 400°C. After keeping warm for 1 hour, it is cooled naturally to room temperature. Take it out of the furnace and polish the surface of the sample with sandpaper.

[0081] ⑧Cold rolling. Cold rolling refers to rolling at room temperature. (1) Rough rolling. A sample with a thickness of about 10 mm is cold rolled at room temperature using a large two-roll mill. During rolling, a total of 5 passes are performed while the roller pressure of the rolling mill remains unchanged in each round of rolling. After rolling, the roller pressure of the rolling mill is adjusted to perform a new round of 5 passes. When the sample thickness is in the range of 7.0 mm to 10.0 mm, the roller pressure is 0.5 mm each time; when the sample thickness is 3.0 mm to 7.0 mm, the roller pressure is 0.2 mm each time; when the sample thickness is 2.0 mm to 3.0 mm, the roller pressure is 0.15 mm each time. When the thickness is less than 2.0 mm, the roller pressure is adjusted to 0.1 mm. After the final rolling, the sample thickness is 1.8 mm to 1.9 mm. (2) Finish rolling. Finish rolling is performed using a four-roll mill. During rolling, the roller pressure of each round of rolling mill is unchanged for a total of 5 rollings, and the roller pressure of the rolling mill is adjusted after rolling for a new round of 5 rollings. When the sample thickness is 1.5mm-1.8mm, the roller pressure is 0.1mm each time, when the sample thickness is 1.0mm-1.5mm, the roller pressure is 0.08mm each time, when the sample thickness is 0.8mm-1.0mm, the roller pressure is 0.05mm each time, when the sample thickness is 0.5mm-0.8mm, the roller pressure is 0.02mm each time, and the last round of rolling pressure is 0.016mm, and the thickness of the rolled sample finally reaches 0.4mm.

[0082] ⑨ The sample obtained by cold rolling is surface treated by grinding with sandpaper with a mesh size greater than 1000 to obtain a high-strength and high-conductivity copper-silver alloy with a smooth surface.

[0083] Figure 1 This is a transmission electron microscopy (TEM) image of the copper-silver alloy prepared in this embodiment; Figure 2 This is a transmission electron microscopy (HAADF) image of the copper-silver alloy prepared in this embodiment; Figure 1 , 2This shows that the high-strength and high-conductivity copper-silver alloy prepared in this embodiment has a synergistic effect on improving the material properties through various microscopic mechanisms such as internal grain refinement, fibers, and dislocations.

[0084] Figure 3 is a stress-strain curve diagram of a tensile test of the copper-silver alloy prepared in this embodiment; Figure 4 is the conductivity distribution diagram of the copper-silver alloy prepared in this embodiment; Figure 3 , 4 It shows that the high-strength and high-conductivity copper-silver alloy prepared in this embodiment has a strength of 1129 MPa, a conductivity distribution of more than 70% IACS, and has good mechanical properties and conductive properties.

[0085] Comparative Example 1

[0086] This comparative example provides a method for improving the performance of a high-strength and high-conductivity copper-silver alloy. The remaining step parameters are the same as those of Example 1, except that: after each heat treatment, water cooling is used instead of natural cooling to room temperature. The water cooling conditions are: after each heat treatment, the sample is in a high temperature state, and the sample is immediately taken out of the high-temperature furnace and placed in cold water for cooling. The cold water temperature is room temperature, and the cooling time is about 5 minutes, and then taken out.

[0087] ① The first forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 450°C, and after keeping the temperature for 1 hour, it is placed in cold water for cooling.

[0088] ② Second forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 400°C, and after keeping the temperature for 1 hour, it is placed in cold water for cooling.

[0089] ③ The third forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 400°C, and after keeping the temperature for 1 hour, it is placed in cold water for cooling.

[0090] After that, forging or rolling is performed, and the forging and rolling parameters are consistent with those in the embodiment, thereby obtaining the final sample. Conductivity test and mechanical test are performed on it, and the conductivity is 73.2% IACS to 74.5% IACS, and the maximum mechanical tensile strength is 946 MPa.

[0091] Comparative Example 2

[0092] This comparative example provides a method for improving the performance of high-strength and high-conductivity copper-silver alloy. The remaining step parameters are the same as those in Example 1, and the only difference is that the conditions of each heat treatment are different.

[0093] ① The first forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 200°C, after keeping the temperature for 1 hour, the temperature is naturally cooled to room temperature.

[0094] ② Second forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 200°C, after keeping the temperature for 1 hour, the temperature is naturally cooled to room temperature.

[0095] ③ The third forging and heat treatment. The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 200°C, and after keeping warm for 1 hour, it is naturally cooled to room temperature. After the heat treatment, rolling is carried out, and the rolling parameters are consistent with the embodiment. The thickness is about 5mm, about 2mm, and about 0.4mm, respectively. A heat treatment of 200°C and 1 hour is carried out to obtain the final sample. The conductivity and mechanical properties are tested. The conductivity is 84.9% IACS~87.4% IACS, and the conductivity is improved. However, the maximum mechanical tensile strength is 688MPa, which is significantly lower than the embodiment, indicating that improper heat treatment process will have an adverse effect on the mechanical properties of the material.

[0096] Comparative Example 3

[0097] This comparative example provides a method for improving the performance of high-strength and high-conductivity copper-silver alloy. The remaining step parameters are the same as those in Example 1, and the only difference is that the conditions of each heat treatment are different.

[0098] ① The first forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 600°C, after keeping the temperature for 1 hour, the temperature is naturally cooled to room temperature.

[0099] ② Second forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 600°C, after keeping the temperature for 1 hour, the temperature is naturally cooled to room temperature.

[0100] ③ The third forging and heat treatment: The forging parameters are consistent with those in the embodiment, and the heat treatment conditions are: the temperature is 600°C, after keeping the temperature for 1 hour, the temperature is naturally cooled to room temperature.

[0101] After the heat treatment, rolling is performed, and the rolling parameters are consistent with the embodiment. Finally, the final sample is obtained, and the conductivity and mechanical properties are tested. The conductivity is 77.4% IACS~80.2% IACS, and the conductivity is improved. However, the maximum mechanical tensile strength is 638 MPa, which is significantly lower than the embodiment, indicating that excessively high heat treatment temperature has an adverse effect on the mechanical properties of the material.

[0102] Comparative Example 4

[0103] This comparative example provides a method for improving the performance of a high-strength and high-conductivity copper-silver alloy. The remaining step parameters are the same as those in Example 1, except that the order of each heat treatment is different. Heat treatment is performed first, and then subsequent processes are performed.

[0104] ① The first heat treatment and forging. The heat treatment conditions are: the temperature is 450°C, after keeping the temperature for 1 hour, it is cooled naturally to room temperature. The forging parameters are consistent with the embodiment.

[0105] ② Second heat treatment and forging. The heat treatment conditions are: temperature is 400°C, after keeping the temperature for 1 hour, it is cooled naturally to room temperature. The forging parameters are consistent with the embodiment.

[0106] ③ The third heat treatment and forging. The heat treatment conditions are: the temperature is 400°C, after keeping the temperature for 1 hour, it is cooled naturally to room temperature. The forging parameters are consistent with the embodiment.

[0107] After forging is completed, rolling is carried out, and the rolling parameters are consistent with the embodiment. Shortly after rolling, the sample begins to break in the middle. It can be seen that the plasticity of the sample at this time is poor, which makes processing impossible, and it is also impossible to prepare specimens with the same size as the embodiment and other comparative examples for mechanical strength and conductivity testing. Therefore, the mechanical tensile strength and conductivity data of the comparative example samples are missing.

[0108] Comparative Example 5

[0109] This comparative example provides a method for improving the performance of high-strength and high-conductivity copper-silver alloy. The remaining step parameters are the same as those in Example 1, and the only difference is that this comparative example does not use forging, but uses rolling technology throughout.

[0110] ① The first rolling and heat treatment. After the first rolling to about 20.5-21.0 mm, heat treatment begins. The heat treatment conditions are: temperature 450°C, keep warm for 1 hour, and then cool naturally to room temperature.

[0111] ② Second rolling and heat treatment: After the second rolling to a thickness of about 15.8-16.3 mm, heat treatment begins. The heat treatment conditions are: temperature 400°C, keep warm for 1 hour, and then cool naturally to room temperature.

[0112] ③ The third rolling and heat treatment. After the second rolling to a thickness of 9.0 mm to 10.1 mm, heat treatment begins. The heat treatment conditions are: temperature 400 ° C, after keeping warm for 1 hour, naturally cool down to room temperature.

[0113] Afterwards, subsequent rough rolling and finish rolling were performed, and the rolling parameters were consistent with those in the embodiment, thereby obtaining the final sample. Conductivity test and mechanical test were performed on the sample, and the conductivity was 70.2% IACS to 71.1% IACS, and the maximum mechanical tensile strength was 903 MPa.

[0114] The properties of the specimens were measured using the following test methods:

[0115] The test methods for mechanical properties tests mainly refer to standards such as GB / T 228.1-2021 "Tensile Test of Metallic Materials Part 1: Room Temperature Test Method". The sample is prepared along the rolling direction and processed into a rectangular cross-section specimen using a wire cutting machine for tensile testing. The parallel width of the middle part of the specimen is 12.5mm and the gauge length is 50mm. The processing process is kept fully cooled to avoid work hardening on the surface or softening due to excessive temperature. The tensile test is carried out on a tensile testing machine at room temperature. The testing machine is equipped with an extensometer to measure and record the tiny plastic deformation of the specimen. The sample is installed in the tensile testing machine for testing. The testing machine records the stress-strain curve of the sample during the test. According to the test data, the tensile strength and other mechanical information of the sample can be obtained. The conductivity of the sample is measured using the sigma2008 digital eddy current metal conductivity meter produced by Xiamen Tianyan Instrument Co., Ltd.

[0116] In summary, the results of the embodiments and comparative examples are as follows:

[0117] Conductivity / %IACS Tensile strength / MPa Example 71.9~72.8 1129 Comparative Example 1 73.2~74.5 946 Comparative Example 2 84.9~87.4 688 Comparative Example 3 77.4~80.2 638 Comparative Example 4 (fracture) (fracture) Comparative Example 5 70.2~71.1 903

[0118] The above describes and evaluates the efficacy of some embodiments of the present invention. It should be understood that the present invention is not limited to the above specific implementations. Any technician familiar with the art can use the above disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solutions of the present invention still falls within the scope of protection of the technical solutions of the present invention.

Claims

1. A method for improving the performance of high-strength and high-conductivity copper-silver alloy, characterized in that: The following steps are involved: S1. Using high-purity copper and high-purity silver as raw materials, sequentially performing vacuum induction melting, casting, and solidification to obtain a copper-silver alloy ingot; S2, forging the copper-silver alloy ingot obtained in step S1 for multiple times, performing a heat treatment after each forging, and then naturally cooling to room temperature to obtain a homogenized ingot; S3, cold rolling the homogenized ingot obtained in step S2 to obtain a copper-silver alloy sample; S4. Surface treatment is performed on the copper-silver alloy sample obtained in step S3 to obtain a high-strength and high-conductivity copper-silver alloy.

2. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 1, characterized in that: In step S1, the high-purity copper is copper particles with a purity of 99.999% and a particle size of φ3×3mm; the high-purity silver is silver particles with a purity of 99.99% and a particle size of φ2×5mm; And / or, the usage ratio of high-purity copper to high-purity silver is 76:

24.

3. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 1, characterized in that: In step S1, the vacuum induction melting process specifically includes the following steps: (1) The raw materials are placed in a vacuum melting furnace, and the furnace body is pre-evacuated. When the vacuum degree is 1Pa, argon is introduced to make the pressure in the furnace 50kPa, and the addition of argon is stopped; the vacuum is continued to be reduced to 1Pa, and argon is introduced again to make the pressure in the furnace 50kPa; the vacuum is then reduced to 1Pa, and then high vacuum is continued to be drawn to 4.8×10 -3 Pa; (2) Argon gas is introduced to 50 kPa, and the furnace heating module is turned on for smelting. The initial heating current is 4.5 A, and then it is increased to 20-22 A at a rate of 1 A per minute. At this time, the temperature inside the furnace is 1000-1100°C. Maintain it for 10-15 minutes to complete the smelting.

4. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 1, characterized in that: In step S1, a circulating water cooling structure mold is used for casting; the mold temperature is maintained at 22-24°C; and / or, the setting time is 2 to 3 hours; And / or, after solidification, the ingot is subjected to rough surface processing and then polished with sandpaper to obtain a rectangular ingot with a thickness of 22 to 24 mm and no surface cracks.

5. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 4, characterized in that: In step S2, the process of multiple forging and heat treatment after forging specifically includes the following steps: (1) First round forging and heat treatment: The copper-silver alloy ingot is subjected to a first round forging, which consists of multiple forgings, and the pressing amount of each forging is controlled at 0.4 mm to 0.5 mm. After forging, the thickness of the ingot is 20.5 to 21.0 mm; then the forged ingot is placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, the ingot is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper; (2) Second forging and heat treatment: The ingot treated in step (1) is subjected to a second round of forging, which consists of multiple forgings, each with a deformation of 10% to 15%, and the thickness of the ingot after final forging is 15.8 to 16.3 mm; then the forged ingot is placed in a heat treatment furnace for heat treatment, and after the heat treatment is completed, it is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper; (3) Third forging and heat treatment: The ingot treated in step (2) is subjected to a third round of forging, which consists of multiple forgings, each with a deformation of 10% to 15%, and the thickness of the ingot after final forging is 9 to 10 mm; the forged ingot is then placed in a heat treatment furnace for heat treatment. After the heat treatment is completed, the ingot is naturally cooled to room temperature, taken out, and the surface of the sample is polished with sandpaper.

6. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 5, characterized in that: The conditions for heat treatment after the first forging are: vacuum degree ≤ 100Pa, temperature 420-450°C, time 1-1.2h; And / or, the conditions for heat treatment after the second forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., time 1-1.2 h; And / or, the conditions for heat treatment after the third forging are: vacuum degree ≤ 100 Pa, temperature 380-400° C., and time 1-1.2 h.

7. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 5, characterized in that: In step S3, the cold rolling process includes rough rolling and finish rolling.

8. The method for improving the performance of high-strength and high-conductivity copper-silver alloy according to claim 7, characterized in that: The rough rolling process specifically includes: rough rolling with a two-roll rolling mill; in each round of rolling, the roller pressure of the rolling mill remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the roller pressure of the rolling mill is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is in the range of 7.0mm to 10.0mm, the roller pressure is 0.5mm each time; when the ingot thickness is 3.0mm to 7.0mm, the roller pressure is 0.2mm each time, and when the ingot thickness is 2.0mm to 3.0mm, the roller pressure is 0.15mm each time; when the ingot thickness is less than 2.0mm, the roller pressure is adjusted to 0.1mm, and after the final rolling, the ingot thickness is 1.8mm to 1.9mm; And / or, the finishing rolling process specifically includes: finishing rolling with a four-roll rolling mill; in each round of rolling, the rolling mill's roller pressure remains unchanged, and a total of 5 rolling passes are performed, and after rolling, the rolling mill's roller pressure is adjusted to perform a new round of 5 rolling passes; when the ingot thickness is 1.5mm~1.8mm, the roller pressure is 0.1mm each time, when the ingot thickness is 1.0mm~1.5mm, the roller pressure is 0.08mm each time, when the ingot thickness is 0.8mm~1.0mm, the roller pressure is 0.05mm each time, when the ingot thickness is 0.5mm~0.8mm, the roller pressure is 0.02mm each time, the last round of rolling pressure is 0.016mm, and the ingot thickness finally reaches 0.4mm.

9. A high-strength and high-conductivity copper-silver alloy, characterized in that: The high-strength and high-conductivity copper-silver alloy is prepared by the method for improving the performance of the high-strength and high-conductivity copper-silver alloy as described in any one of claims 1 to 8.

10. The high-strength and high-conductivity copper-silver alloy according to claim 9, characterized in that The tensile strength of the high-strength conductive copper-silver alloy is above 1000 MPa, and the electrical conductivity is above 70% IACS.

Citation Information

Patent Citations

  • Preparation method for Cu-Ag alloy with high-strength and high-conductivity performance

    CN106676314A

  • Preparing method for copper-silver alloy target material

    CN107937878A

  • High-strength and high-conductivity copper-silver alloy wire and preparation method thereof

    CN114645153A

  • Preparation method and application of endogenous fiber reinforced copper-silver alloy plate

    CN117926048A

  • Preparation method of high-strength and high-conductivity Cu-Ag alloy wire

    CN118455300A